EFEKTIVITAS PENGAWASAN MODEL PEMBELAJARAN TEMATIK PADA KURIKULUM 2013 - Hartono, Meilani; Sapoetra, Jimmy (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to investigate the effectiveness of using the supervision model based on thematic learning in 2013 curriculum. The study used qualitative approach and the data were taken from several public elementary schools in Palmerah, West Jakarta. The techniques used to collect the data were interview, questionnaire and documentation. Data validity were tested with credibility, transferability, dependability, and comfortability. The model developed was validated using the Delphi technique. The result of this research was the discovery of the model and device- based supervision model of professional competence of primary teachers in integrated learning. The long-term goal of this research is to improve the teachers’ competence and the supervision quality for primary teachers in integrated learning